MODELLING TRANSBOUNDARY AIR POLLUTION IN ASEAN WITH GAME THEORY - Abenita Christien, Nathasya
Air pollution is a crucial problem that is faced by humans and the environment. This problem is often a transboundary problem since pollution from an area can be transferred to another. In ASEAN, transboundary pollution between countries has happened routinely until now. Furthermore, this problem can be seen as conflict between countries. To understand this problem, we need a method to analyze the behavior of each country. Game theory is a mathematical approach to analyze conflict between individuals. With game theory, countries in ASEAN are seen as players. With differential game, the pollution stock of a country is represented as system state. Pollution of a country influences the pollution in its neighboring countries. During the game, each country in ASEAN takes a decision that represents the investment rate to a more environmentally-friendly (clean) policy. When a country wants to optimize its condition, it minimizes its pollution cost. Pollution cost is defined as environmental damage and clean policy investment cost. In this research, countries in ASEAN will be observed behaving in three variations– noncooperative, basic imitation, and advanced imitation. When behaving noncooperatively, each country wants to optimize their own condition. When behaving basic imitation, each country chooses to imitate the neighboring countries’ decision by considering the average difference of investment strategy with neighboring countries. When behaving advanced imitation, neighbor country that is successful to have lower pollution cost has bigger influence. When ASEAN countries behave noncooperatively, each country can reduce their pollution stock to small values. This process takes a long time with more than one decade. When countries imitate each other, each country can reduce their pollution stock to zero much quicker.